One-step electroplating of palladium–copper alloy layers on a vanadium membrane for hydrogen separation: Quick, easy, and low-cost preparation. (16th September 2021) - Endo, Naruki; Dezawa, Norikazu; Komo, Yasuhiro; Maeda, Tetsuhiko
Abstract: Palladium–copper (PdCu) alloy layers with 150 nm thickness were prepared by one-step electroplating on both sides of a vanadium foil. The entire process, including pretreatment, washing, and electroplating, was complete in <5 min. The PdCu layer had a high surface coverage and almost completely covered the vanadium foil. The composition difference between the center and the edges was within 3 at%, and the alloy composition was controlled to nearly the target composition (50:50). Peel tests revealed that the as-electroplated layer had sufficient adhesion for practical applications. XRD analysis confirmed the successful formation of a face-centered cubic (FCC) PdCu alloy. In-situ XRD analysis performed under a hydrogen atmosphere revealed the structural change of PdCu from FCC to body-centered cubic (BCC) immediately after the temperature reached 300 °C. The hydrogen permeability of electroplated PdCu/V/PdCu at 200–300 °C (1–3 × 10 −8 mol m −1 s −1 Pa −1/2 ) was considerably higher than that of the 10 μm-thick electroplated BCC PdCu. Highlights: 150 nm-thick PdCu alloy layers were electroplated on both sides of a vanadium foil. As-electroplated PdCu layer had sufficient adhesion for practical application. FCC PdCu changed to BCC PdCu at 300 °C. Electroplated PdCu/V/PdCu exhibited high hydrogen permeability. The one-step electroplating process is a quick, easy, and inexpensive method.